Chapter 1 Introduction - Liu, zhongbo (Taylor & Francis, 2024)
This book examines science and technology policies in China over time and explores the development of scholarly communication through the lens of the political economy of communication. Despite political censorship and restrictions on the production of academic knowledge in China, the number of scholarly publications has skyrocketed over the past 20 years. By explaining these seemingly contradictory phenomena, this study provides insight into the complex landscape of scholarly communication in China, shaped by the government in collaboration with commercial publishers. The book examines the dynamic relationship between the state and the market, including their key players, which determines the production and dissemination of academic knowledge. From a political economy perspective, it investigates how the academic governance complex, a system that intertwines communication, politics, and economics, has been established in China. It then discusses the impact of this system on the production of academic knowledge in the country. The title will serve as a key reference for academics, researchers, and students interested in the intersection of communication studies, librarianship, and political science, particularly those focusing on China's academic knowledge production and scholarly communication.